Fish stock estimation in Sikka Regency Waters, Indonesia using Single Beam Echosounder (CruzPro fish finder PcFF-80) with hydroacoustic survey method - Muhammad Zainuddin Lubis; Wenang Anurogo (Syiah Kuala University, 2016)
Sikka regency waters including fishery management with a high utilization status so that the necessary stages of an intensive monitoring and research potential of fish resources. This study aimed to obtain the estimated value of stock biomass and density of fish resources with the acoustic method. Quantitative data obtained will be a source of current information on the state of fish resources in the Sikka regency waters, Indonesia. The research was conducted in May 2015. Acoustic data retrieval, using instruments CruzPro fish finder PcFF-80 with sound velocity of 1516 m / s, power 2560 Watt, and method in survey acoustic use hydroacoustic long transect. The horizontal distribution shows a fluctuation striking at research location has the highest salinity levels in the range of 29.3-29.8 psu. Total biomass of fish in this study showed more the number is at a depth of 11-20 m that is 2,008 tons/km and at a depth of 1-10 m have the total fish biomass is 12.33 tons/km, single detection is done using a single target hydroacoustic show more dominance at a depth of 11-20 m in Sikka regency waters, MTB, Indonesia in May 2015. Number of data from results obtained by looking at the relationship between the number of the data with the total biomass in 1-10 m depth has equation Y = 0.0967x + 0.0486 with R2 is 0.0464 (4%) , while at a depth of 11-20 m has a regression equation is Y = 0.0003x + 0041 with the R2 is 0.0091 (0.9%). Variations in the data or the detection of single targets have variations over the data that is at a depth of 11-20 m with the lowest regression is 0.9%.Keywords: Hydroacoustic, Salinity, Biomass, Stock estimation, Sikka regency waters.